Understanding the link between circumferential dikes and eruptive fissures around calderas based on numerical and analog models - Fabio Corbi; Eleonora Rivalta; Virginie Pinel; Francesco Maccaferri; Valerio Acocella (Geophysical Research Letters)
Abstract Active calderas are seldom associated with circumferential eruptive fissures, but eroded magmatic complexes reveal widespread circumferential dikes. This suggests that, while the conditions to emplace circumferential dikes are easily met, mechanisms must prevent them from reaching the surface. We explain this discrepancy with experiments of air injection into gelatin shaped as a volcano with caldera. Analog dikes show variable deflection, depending on the competition between overpressure, Pe, and topographic unloading, Pl; when Pl/Pe = 4.8–5.3, the dikes propagate orthogonal to the least compressive stress. Due to the unloading, they become circumferential and stall below the caldera rim; buoyancy is fundamental for the further rise and circumferential fissure development. Numerical models quantitatively constrain the stress orientation within the gelatin, explaining the observed circumferential dikes. Our results explain how dikes propagate below the rim of felsic and mafic calderas, but only in the latter they are prone to feed circumferential fissures.